2013
DOI: 10.1248/bpb.b12-00991
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Promotes Survival of Cerebral Cortex Neurons with Simultaneous Addition of [Fe(II)(β-Citryl-L-glutamate)] Complex in Primary Culture

Abstract: It has been reported that the activity of mitochondrial aconitase (m-aconitase) is rapidly inhibited in a variety of cells when exposed to nitric oxide (NO).NO is a free radical produced by a wide variety of cell types, that reacts predominantly with Fe(III) or Fe(II) ions of heme proteins and Fe-S centers, as well as molecular oxygen, and superoxide anion. 4,5) Moreover, NO easily reaches mitochondria from cytosolic or extracellular sources, due to its low molecular radius and hydrophobic nature.6) It has als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…BCG was first identified in newborn rats and thought to play a role during brain development, and enzymes synthesizing and degrading BCG were recently described . During brain development, iron concentration should be tightly regulated, and it has recently been demonstrated that BCG acts as an iron carrier to activate aconitase. , The BCG concentration has been found to be elevated during growth and differentiation of neurons and during anaerobic metabolism in rats, and its iron-binding capacity suggests that BCG may enhance cell viability and accelerate mitochondrial activities through the direct transfer of iron to aconitase (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…BCG was first identified in newborn rats and thought to play a role during brain development, and enzymes synthesizing and degrading BCG were recently described . During brain development, iron concentration should be tightly regulated, and it has recently been demonstrated that BCG acts as an iron carrier to activate aconitase. , The BCG concentration has been found to be elevated during growth and differentiation of neurons and during anaerobic metabolism in rats, and its iron-binding capacity suggests that BCG may enhance cell viability and accelerate mitochondrial activities through the direct transfer of iron to aconitase (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“… 40 , 41 β-Citrylglutamate may act as a chaperone for iron to aconitase and protective complex against NO-induced aconitase inhibition. 42 , 43 Malylglutamate may form similar complexes to aid biochemical processes or protect the worm against metal burdens. The physiological functions of malylglutamate need further exploration to understand its unique presence and abundance in earthworms.…”
Section: Discussionmentioning
confidence: 99%